Black Religion - Hart, W. author. aut Link
XIII, 228 p.
Keywords: This book explores the spiritual dimensions (political, racial, sexual, and violent) of Malcolm X's journey from Christianity to Islam, Julius Lester's journey from Christianity to Judaism, and Jan Willis's journey from Christianity to Buddhism.